Islam, Securitization, and US Foreign Policy - Shipoli, Erdoan A. (Springer International Publishing, 2018)
This book argues that Islam has been securitized in US foreign policy, especially during the W. Bush administration when it was increasingly portrayed as the ultimate "other." This securitization was realized through the association of Islam with unique security threats in speeches of foreign policy and national security. By analyzing the four recent US presidents' discourses on Islam, this work sheds light on how they viewed Islam and addresses the following questions: How do we talk about Islam, its place and relationship within the context of US security? How does the language we use to describe Islam influence the way we imagine it? How is Islam constructed as a security issue? Erdoan A. Shipoli is Visiting Scholar at the Center for Muslim-Christian Understanding at Georgetown University, USA. He is also a social entrepreneur and has established numerous international organizations to advance dialogue, leadership, and youth development.